CRISPR/Cas13a-assisted AMP generation for SARS-CoV-2 RNA detection using a personal glucose meter - Junhyun Park; Hyogu Han; Jae Hoon Jeung; Hyowon Jang; Chihyun Park; Jun Ki Ahn (Biosensors and Bioelectronics: X, 2022)
Herein, we described a washing- and label-free clustered regularly interspaced short palindromic repeats (CRISPR)/LwaCas13a-based RNA detection method utilizing a personal glucose meter (PGM), which relies on the trans-cleavage activity of CRISPR/Cas13a and kinase reactions. In principle, the presence of target RNA activates the trans-cleavage of CRISPR/Cas13a, generating 2′,3′-cyclic phosphate adenosine, which is converted to adenosine monophosphate (AMP) by the T4 polynucleotide kinase. Subsequently, the AMP is converted to adenosine diphosphate (ADP) through phosphorylation by a myokinase; ADP is then used as a substrate in the cascade enzymatic reaction promoted by pyruvate kinase and hexokinase. The overall reaction leads to the continuous conversion of glucose to glucose-6-phosphate, resulting in a reduction of glucose concentration proportional to the level of target RNA, which can therefore be indirectly measured with a PGM. By employing this novel strategy, severe acute respiratory syndrome coronavirus-2 RNA can be successfully detected with excellent specificity. In addition, we were able to overcome non-specific responses of CRISPR/Cas13a and distinguish single nucleotide polymorphisms by introducing a single-base mismatch in the complementary RNA. Our study provides an alternative coronavirus disease 2019 detection technology that is affordable, accessible, and portable with a fast turnaround time and excellent selectivity.